Activation of Sigma Receptors With Afobazole Modulates Microglial, but Not Neuronal, Apoptotic Gene Expression in Response to Long-Term Ischemia Exposure - Behensky, Adam A.; Katnik, Christopher; Yin, Huquan; Cuevas, Javier (Frontiers in Neuroscience, 2019)
Stroke continues to be a leading cause of death and serious long-term disability. The lack of therapeutic options for treating stroke at delayed time points (≥ 6 hr post-stroke) remains a challenge. The sigma receptor agonist, afobazole, an anxiolytic used clinically in Russia, has been shown to reduce neuronal and glial cell injury following ischemia and acidosis; both of which have been shown to play important roles following an ischemic stroke. However, the mechanism(s) responsible for this cytoprotection remain unknown. Experiments were carried out on isolated microglia from neonatal rats and cortical neurons from embryonic rats to gain further insight into these mechanisms. Prolonged exposure to ischemic in vitro ischemia conditions resulted in microglial cell death, which was associated with increased expression of the pro-apoptotic protein, Bax, the death protease, caspase-3, and reduced expression in the anti-apoptotic protein Bcl-2. Incubation of cells with afobazole during ischemia decreased the number of microglia expressing both Bax and caspase-3, and increased cells expressing Bcl-2, which resulted in a concomitant enhancement in cell survival. In similar experiments, incubation of neurons under in vitro ischemic conditions resulted in higher expression of Bax and caspase-3, while at the same time expression of Bcl-2 was decreased. However, unlike observations made in microglial cells, afobazole was unable to modulate the expression of these apoptotic proteins, but a reduction in neuronal death was still noted. The functional state of surviving neurons was assessed by measuring metabolic activity, resting membrane potential, and responses to membrane depolarizations. Results showed that these neurons maintained membrane potential but had low metabolic activity and were unresponsive to membrane depolarizations. However, while these neurons were not fully functional, there was significant protection by afobazole against long-term ischemia-induced cell death. Thus, the effects of sigma receptor activation on microglial and neuronal responses to ischemia differ significantly.